Infrastructure Development and Demographic Dynamics as Drivers of Regional Economic Growth: Evidence from Java Island, Indonesia - Septriani Septriani; Eka Kadharpa Utama (Econetica: Jurnal Sosial, Ekonomi, dan Bisnis, 2024)
Infrastructure has long been recognized as a fundamental driver of economic growth by enhancing productivity, market connectivity, and investment efficiency. This study investigates the impact of road infrastructure, electricity infrastructure, and population on regional economic performance across six provinces in Java Island, Indonesia, during the period 2016–2021. A quantitative approach using panel data regression was employed to analyze secondary data obtained from Statistics Indonesia (BPS), the Ministry of Finance, and the Ministry of Public Works and Housing. The Random Effect Model (REM) was identified as the most appropriate specification based on the Chow, Hausman, and Lagrange Multiplier tests. The results show that both road and electricity infrastructures have a positive and statistically significant influence on Gross Regional Domestic Product (GRDP), confirming the crucial role of physical capital accumulation in supporting regional productivity. In contrast, population growth does not significantly affect GRDP, indicating that demographic expansion alone cannot guarantee economic gains without parallel improvements in human capital quality and labor absorption. The findings underscore that infrastructure investment must be accompanied by human development strategies and regional planning policies to achieve inclusive and balanced economic growth. This study contributes to empirical literature on regional development economics and provides evidence-based insights for policymakers in developing economies seeking to enhance spatial equity and sustainable growth.